PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA GURU DIMODERASI GAYA KEPEMIMPINAN (Studi pada Guru SMP Negeri di Wilayah Kecamatan Ulujami Kabupaten Pemalang) - Teguh Purnomo, 1352020070; Sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the influence of motivation and discipline to the performance of teachers with leadership style is moderated. The specific objectives of the study was to examine and analyze the effect of motivation on teacher performance, the influence disciplinary on teacher performance, the influence of leadership style on teacher performance, the role of the moderating influence of motivational leadership style on teacher performance, and the role of the moderating influence of disciplined leadership style on teacher performance. This research is an explanatory research study that proves the effect of motivation and discipline to the performance of teachers with leadership style is moderated. This study uses the study population (census) amounted to 127 respondents. Data of this research is primary data obtained directly from the source. The method of data analysis using a model of moderation with a quasitype interaction techniques. The results showed that work motivation positive effect on teacher performance Ulujami Junior High School in the District Pemalang; Dsiplin influential work on teacher performance Ulujami Junior High School in the District Pemalang; The style of leadership does not affect the performance of teachers Junior High School in District Ulujami Pemalang; The style of leadership does not moderate the influence of motivation to work on teacher performance and leadership style did not moderate the influence of labor discipline on teacher performance. Theoretical implications, and recommendations for future research are also discussed in the final part in this study. Keywords : Motivation, Discipline, Leadership Style and Teachers Performance